PENERAPAN STRATEGI CATATAN TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN ZAMAN PRA-AKSARA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS IV MI ISLAMIYAH PAKEL MONTONG TUBAN - Dewi Niswatul Fithriyah; Moh Nur Fadlil; Nur Nafisatul Fithriyah (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2020)
Research is motivated by the low student learning process and also the weak learning process that is still centered on the teacher. Teaching and learning activities that are always discussed by the teacher will result in low student learning activities in school. The subjects in this class action research were grade IV MI Islamiyah Pakel Montong Tuban students. As an effort that can be done to overcome these problems, then this is by implementing a guided note strategy. Through a record of guided strategies, students will be asked to participate in teaching and learning activities and students will be better prepared and able to discuss the material being studied in action, observation, and reflection. The results showed that the application of guided strategy notes to the pre-literate epoch material of social science subjects was carried out smoothly and very well. Proof can also be known from the value generated by students in working on LK outlining the contents of the text that discusses the history of pre-literacy and also describes lessons that can be drawn from the history of pre-literate community life with the percentage of classical learning completeness 66.6% in the first cycle and 83, 3% in the second cycle.